The COVID-19 pandemic and leisure providers—Challenges, opportunities and adaptation strategies for ski area operators in Austria - Steiger, Robert; Graiff, Lukas; Peters, Mike; Schnitzer, Martin (Frontiers in Sustainable Tourism, 2023)
The COVID-19 crisis and the related nationwide lockdowns reduced the available types of physical activity, especially in the winter season. Besides closed indoor sports facilities, some outdoor sports were also inaccessible because of curfews and/or the closure of outdoor sports facilities. However, in Austria, the operation of alpine ski areas was permitted even during the full lockdown in the winter season 2020/21, albeit under strict hygiene requirements and capacity restrictions. This posed a challenge for ski area operators, with those heavily dependent on foreign multi-day guests facing severe declines in demand due to closed accommodation and closed borders while others were challenged by demand pressures from nearby population centers. We therefore want to examine how Austrian ski area operators managed these challenges, how they evaluated this extraordinary season and whether these new experiences and established measures can be used to improve customer experience in the future. We used a mixed-methods approach with a quantitative survey (n=65) and follow-up qualitative interviews with managers (n=20) of Austrian ski areas. For 75 % of respondents, the reason for keeping the ski areas open, despite the fact that 95 % suffered average revenue declines of 80 %, was to provide an outlet for physical activity for the local population. Respondents noticed a lot of gratitude and growing trust from local customers that could be used to increase the approval of tourism in the local population. The COVID-19 pandemic has also advanced the spread of technological innovations in the cable car industry, such as online ticketing and dynamic pricing. Furthermore, sustainability has become a more important issue with current topics being deceleration and a stronger focus in the future on qualitative rather than quantitative development.